2014
DOI: 10.1080/10454438.2014.959829
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Technical Efficiency in Aquaculture

Abstract: We compared stochastic frontier analysis (SFA) and data envelopment analysis (DEA) methods to calculate mean technical efficiency (MTE) of global aquaculture. A total of 36 published articles on technical efficiency of 55 aquaculture operations were reviewed. SFA yielded lower MTE estimates than DEA. MTE for Asia, Africa, Europe, and the USA was estimated to be 0.64, 0.71, 0.80, and 0.73, respectively, indicating considerable scope for increasing output of aquaculture with the currently available array of inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 36 publications
3
40
2
Order By: Relevance
“…Since DEA MTEs were earlier found to be lower than SFA, the MTEs of distance functions certainly have overshadowed the effect of MTEs from DEA to produce this fi nding. While previous studies showed MTE from translog are higher than those from Cobb-Douglas functions (Bravo-Ureta, 2007;Moreira Lopez and Bravo-Ureta, 2009), recent studies provide contrary evidence, that is, translog functional forms generate lower MTEs than MTEs estimated from Cobb-Douglas functions (Iliyasu et al, 2014;Ogundari, 2014). Since Ogundari (2014) used a logit fractional regression model, his conclusions corroborate that of this study.…”
Section: Discussion Of Selected Estimated Modelsupporting
confidence: 77%
See 3 more Smart Citations
“…Since DEA MTEs were earlier found to be lower than SFA, the MTEs of distance functions certainly have overshadowed the effect of MTEs from DEA to produce this fi nding. While previous studies showed MTE from translog are higher than those from Cobb-Douglas functions (Bravo-Ureta, 2007;Moreira Lopez and Bravo-Ureta, 2009), recent studies provide contrary evidence, that is, translog functional forms generate lower MTEs than MTEs estimated from Cobb-Douglas functions (Iliyasu et al, 2014;Ogundari, 2014). Since Ogundari (2014) used a logit fractional regression model, his conclusions corroborate that of this study.…”
Section: Discussion Of Selected Estimated Modelsupporting
confidence: 77%
“…The statistically insignifi cant parameters imply MTE for OA have not increased signifi cantly over the period. The fi nding of a non-increasing MTE over time for organic agriculture is not different from the earlier conclusions of Thiam et al (2001) and Iliyasu et al (2014) for CA. Indeed, in the literature, multi-country meta-analysis of TE has shown either stagnation or decline in MTE over time.…”
Section: Discussion Of Selected Estimated Modelsupporting
confidence: 38%
See 2 more Smart Citations
“…Iliyasu et al . () aimed at explaining the variability observed in 36 efficiency papers on aquaculture. Fan et al .…”
Section: Meta‐analysis Of Local Government Efficiencymentioning
confidence: 99%